Conflict Of Regional Expansion In Indonesia - Suraji, Ahmad Bakri Putra ,Muhamad Ali Embi (International Journal of Advanced Science and Technology, 2020)
The context of regional expansion which is synergized with decentralization and regional autonomy is the will of reform and regional demands, but in its implementation it is not proportional to the expectations that are the goals of the pemekaran policy. According to Tryatmoko (2010) the issue of local governability is not only marked by weakness or expansion of the results of regional expansion, but also the weakness of the ability of the community to support local political and economic development. Furthermore Tryatmoko (in Ratnawai as Isabella Jenin argues) that the issue of the effectiveness of government policy in governing concerns efficiency and legitimacy. While the issue of consent from the governed includes the involvement of the public in decision making and oversight of the netting of government. In this case, the division of regions needs to receive attention and supervision, and it will gradually carry out and carry out the evaluation in stages.